Measurement of plasma B6 vitamer profiles in children with inborn errors of vitamin B6 metabolism using an LC‐MS/MS method. Issue 1 (11th May 2012) - Footitt, Emma J.; Clayton, Peter T.; Mills, Kevin; Heales, Simon J.; Neergheen, Viruna; Oppenheim, Marcus; Mills, Philippa B.
Abstract: Vitamin B6 dependent seizure disorders are an important and treatable cause of childhood epilepsy. The molecular and biochemical basis for some of these disorders has only recently been elucidated and it is likely that inborn errors affecting other parts of this complex metabolic pathway are yet to be described. In man vitamin B6 ingested from the diet exists as six different vitamers, pyridoxal (PL), pyridoxamine (PM), pyridoxine (PN), pyridoxal 5'‐phosphate (PLP), pyridoxamine 5'‐ phosphate (PMP) and pyridoxine 5'‐phosphate (PNP). Its breakdown product, 4‐pyridoxic acid (PA), is excreted in urine. Here we describe an analytical LC‐MS/MS method to measure all vitameric B6 forms in plasma and have subsequently applied this methodology to investigate children with vitamin B6 responsive seizure disorders. We show that patients with inborn errors of B6 metabolism such as pyridox(am)ine 5'‐phosphate oxidase (PNPO) deficiency have characteristic B6 profiles which allow them to be differentiated from each other and control populations, even when on treatment with B6 . Regardless of diagnosis, patients on treatment doses of pyridoxine hydrochloride and pyridoxal phosphate have markedly elevated levels of some vitameric forms (PLP, PL and PA). Such mega doses of B6 treatment are known to be associated with neurotoxicity. This LC‐MS/MS method will be a useful tool for treatment monitoring and may help further our understanding of mechanisms of neurotoxicity in patient groups.